Long-term accessibility of e-books: challenges, obstacles, responsibilities (Libellarium: journal for research in the field of information and related sciences, 2015)
The traditional life cycle of books has gone through many changes in the digital environment - enough to start questioning the effects of such changes on the process of creating, publishing, distributing, reading and preserving books. This paper focuses on issues concerning the preservation and archiving of published authors’ works in the digital environment for the purpose of their long-term accessibility. The aim of this paper is to give an overview of relevant legal, technical, societal and organisational issues from which challenges, obstacles and responsibilities in ensuring long-term accessibility of e-books arise. Issues related to authorship, editions, changes in content, copyright and digital rights management, selection criteria for preservation, and preservation responsibility will be discussed, specifically focusing on libraries’ and publishers’ roles in this process. The paper is based on a literature review and content analysis aiming to answer two basic research questions: What specific characteristics of e-books influence their preservation possibilities? Who is responsible for long-term accessibility of e-books?
Keywords: e-books; digital preservation; digital curation; preservation management; heritage collections